(untitled) (Research, Society and Development, 2021)
The consumption of homemade mayonnaise has been growing due to its nutritional and sensory characteristics. There are few studies reporting the sanitary quality and intrinsic characteristics of these products served in commercial establishments in Manaus-Amazonas. This study aimed to carry out the microbiological analysis and the physicochemical characteristics of homemade mayonnaise served in snack bars in the city of Manaus, Amazonas. Ten samples were collected in snack bars in the south-central (ZCS), east (ZL), north (ZN), west ZO) and south (ZS) zones. These products were evaluated for the presence of microorganisms (Coliforms at 45 °C, Escherichia coli and Salmonella sp.) and physicochemical characteristics (total titratable acidity and pH). The samples showed low Coliform counts at 45 °C (6.8 NMP/g to 21 NMP/g), absence of E. coli and Salmonella sp. The significant values ​​of acidity (2.90%) and pH (5.32) were determined in samples ZL1 and ZS1, respectively. Homemade mayonnaise served in snack bars in Manaus meet current microbiological standards. The evaluations of the quality parameters of these products must be continuous, considering their high acceptance in the capital of Amazonas.